Um conceito plural: a ἄτη na tragédia grega - Rodrigues, Marco Aurélio [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
In the first half of the twentieth century, E. R. Dodds not only stimulated new perspectives through the book The Greeks and the irrational (1953), but also has become the benchmark for future scholars to discuss the concept of ἄτη in the Iliad. Extremely complex, the word ἄτη means in the first instance a blinding stage of human thought and, later, the very accomplished disgrace. Suzanne Saïd (1978) adds that later in classical tragedy, the concept would refer to all sorts of misfortunes. It was R. Doyle (1984) who analyzed the concept in all classical tragedies, just trying to establish its different meanings. Thus, this thesis aims to defend that the concept of ἄτη, along the classical Greek tragedy in the fifth century BC, undergoes changes, assuming different meanings according to the context presented, and may even have lost its original meaning, that the epic and all previous literature recorded. In addition, being united with other terms, the concept of ἄτη achieves new contours and different meanings, which prevents its translation to be fixed at a single semantic field. Hence the proposal, also, to point out that the translation respects the proper use made in each of the tragedies by their authors. Therefore, the argument permeates all the classic tragedies of Aeschylus, Sophocles and Euripides in which the word is present (twenty-eight), in which the term indicates change or addition of semantic value, a fact that will be based on the analysis of the transformation of thought of the Greek man, along the fifth century, underwent extreme changes from the foundation of democracy and the victory against the Persians, until the end of the Peloponnesian War, the fall of the Athenian power and the development of rational thought

Na primeira metade do século XX, E. R. Dodds não apenas estimulou novas perspectivas com o livro The Greeks and the irrational (1953), como tornou-se referência aos futuros estudiosos ao discutir o conceito de ἄτη na Ilíada. Extremamente complexo, o vocábulo ἄτη designa, em primeira instância, um estágio de cegueira do pensamento humano e, mais tarde, a própria desgraça consumada. Suzanne Saïd (1978), acrescenta que, posteriormente, na tragédia clássica, o conceito passaria a fazer referência a toda sorte de infortúnios. Foi R. Doyle (1984) quem fez a análise do conceito em todas as tragédias clássicas, apenas tentando estabelecer seus diferentes sentidos. Dessa forma, a presente tese tem por objetivo defender que o conceito de ἄτη, ao longo da tragédia clássica grega, no século V a.C., passa por mudanças, assumindo diferentes acepções de acordo com o contexto apresentado, podendo, inclusive, ter perdido seu sentido original, aquele que a épica e toda a literatura anterior registravam. Para além disso, ao estar unido a outros termos, o conceito de ἄτη ganha novos contornos e significados diferentes, o que impede que sua tradução seja fixada em um único campo semântico. Daí a proposta, também, de pontuar que sua tradução respeite o uso adequado feito em cada uma das tragédias por seus autores. Para tanto, a tese perpassa todas as tragédias clássicas de Ésquilo Sófocles e Eurípides em que o vocábulo está presente (vinte e oito), nas quais o termo indica mudança ou acréscimo de valor semântico, fato este que será fundamentado na análise da transformação de pensamento do homem grego que, ao longo do século V, passou por mudanças extremas, desde a fundação da democracia e a vitória contra os persas, até o fim da Guerra do Peloponeso, com a queda do poderio ateniense e o desenvolvimento do pensamento racional
Keywords: Ésquilo; Sofocles; Eurípides; Literatura classica; Literatura grega; Tragedia; Greek literature